EFFECTIVENESS OF CYCLONE TUNNELS AS TOILET VENTILATOR FOR GREEN ARCHITECTURE - GUNAWAN GUNAWAN; Fibria Conytin Nugrahini (PURWARUPA Jurnal Arsitektur, 2020)
Abstract.Highest usage of energy to the air condition will be ever accompanied by the increasing of Glass house Gas productivity, owning flimsy impact of Ozone coat in Atmosphere. Really this phenomenon in future will be more concern, the important thing in city area that loaded high rise building. For that to all architects along with their stakeholder who required doing the effort accompanied with variety of innovation and also creation that based on action of energy economically. Existence of Structure System of Core at laminated building of many floors (high rise building) where the shape was looked like flue roof boosting to follow height of building, can be processed and dimulty functioned as component of natural evaporation system by giving addition some elements among others, mow (duct) vertical - horizontal, room or funnel for cross section of temporary air, baling-baling (cyclone) and grill. With this natural evaporation method, the assumption can do to transfer of air at least at restroom or toilet area at high rise. Functionalism of core was as flue of natural evaporation meant as adding effort on exchequer of Green Architecture. Keyword: economical of energy, gas of glass house, green architecture AbstrakSemakin tingginya penggunaan energi untuk pengkondisian udara, akan senantiasa diiringi oleh  meningkatnya produktivitas Gas Rumah Kaca, yang memiliki dampak menipisnya lapisan Ozon di Atmosfir. Sungguh fenomena ini kedepan akan semakin  memprihatinkan, utamanya di kawasan perkotaan yang sarat bangunan tinggi. Untuk itu bagi para arsitek beserta steakholder-nya perlu melakukan upaya yang diiringi dengan ragam inovasi serta kreasi  yang berbasis pada tindakan hemat energi. Keberadaan Sistem Struktur Core pada bangunan berlapis lantai banyak ( high rise building) dimana bentuknya telah menyerupai bumbung cerobong yang menjulang mengikuti ketinggian bangunan, dapat diolah dan dimulti fungsikan sebagai komponen Sistem penghawaan alamiah dengan memberikan tambahan beberapa elemen diantaranya, selumbung (duct)  vertikal – horizontal, ruang atau corong penampung udara sementara, bailng-baling (cyclone) dan kisi-kisi (grill). Dengan metoda penghawaan alamiah ini, diasumsi dapat melakukan pertukaran udara sedikitnya pada area lantai dasar untuk gedung empat lantai keatas. Fungsionalisasi core sebagai cerobong penghawaan alamiah dimaksudkan sebagai upaya penambah perbendaharaan Green Architecture. Kata kunci: Arsitektur hijau, Gas rumah kaca, Hemat energi